2007
DOI: 10.1016/j.amepre.2007.05.007
|View full text |Cite
|
Sign up to set email alerts
|

A Review of eHealth Interventions for Physical Activity and Dietary Behavior Change

Abstract: Objective-To review eHealth intervention studies for adults and children that targeted behavior change for physical activity, healthy eating, or both behaviors.Data Sources-Systematic literature searches were performed using five databases: Medline, PsychInfo, CINAHL, ERIC, and the Cochrane Library to retrieve articles. Study Inclusion and ExclusionCriteria-Articles published in scientific journals were included if they evaluated an intervention for physical activity and/or dietary behaviors, or focused on wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
460
0
9

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 548 publications
(486 citation statements)
references
References 67 publications
17
460
0
9
Order By: Relevance
“…We also identified 5 prior systematic reviews evaluating relevant studies published prior to January 2011, each including from 7 to 36 studies 9, 10, 11, 12, 13. Table 3 summarizes the characteristics and findings of these reviews.…”
Section: Resultsmentioning
confidence: 99%
“…We also identified 5 prior systematic reviews evaluating relevant studies published prior to January 2011, each including from 7 to 36 studies 9, 10, 11, 12, 13. Table 3 summarizes the characteristics and findings of these reviews.…”
Section: Resultsmentioning
confidence: 99%
“…45 Third, poor compliance is recognized as a major issue in most online studies. 46 Actually, several studies have reported that compliance or levels of Internet usage were found to be associated with weight loss. 10,20,23,32,[47][48] However, quite a few of the studies included in this meta-analysis did not provide information on compliance (for example, Website log-in frequency).…”
Section: Discussionmentioning
confidence: 99%
“…Many of the reasons that make Internet approaches promising may apply to smartphone apps. The treatment effect sizes of Internet-based approaches are not large, but their potential to reach a large audience could result in a meaningful public health impact [14]. Some of the reasons that Internet platforms are efficacious may be due to ability to provide a tailored experience along with the ease of self-monitoring [12,15,16].…”
Section: Introductionmentioning
confidence: 99%